Designing Nonpolar Metallic Interfaces using Insulating Transition Metal Olivine Phosphates. Issue 2 (7th February 2018) - Jena, Ajit; Murali, Devaraj; Nanda, Birabar Ranjit Kumar
Abstract: Through density functional calculations, we have demonstrated that ferromagnetic and metallic (FM‐M) phase can be tailored in superlattices consisting of two dissimilar antiferromagnetic and insulating olivine phosphates LiMPO4 and LiMʹPO4 where M and Mʹ are 3 d transition metals. The proposed tailored superlattices are stable and differ from the regular superlattices through broken and missing PO4 tetrahedra. As a result, the p–d covalent bondings become reasonable and transition metal ions are forced to stabilize in fractional charge state instead of the integer‐charge state observed in bulk. These result in partially occupied parabolic dispersive bands to favor the metallic phase and therefore open up the possibilities to go beyond the conventional layered perovskite polar interfaces to create metallic heterostructures out of insulating oxides. Out of all M‐Mʹ combinations, we find that Cr‐Mn, Cr‐Co, Cr‐Ni, Mn‐Co and Mn‐Ni combinations yield the FM‐M phase as ground state in the tailored superlattices. Abstract : Electronic structure calculations are performed on antiferromagnetic and insulating olivine phosphate‐based superlattices in order to explore novel quantum states not exhibited by the bulk. Metallic ferromagnetic states are realized in certain tailor‐made superlattices, thereby providing the scope to go beyond the conventional polar and planar oxide heterostructures to create conducting interfaces out of insulating nonplanar oxides.